2015
DOI: 10.1080/02640414.2015.1020841
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of genetic variants between proficient low- and high-risk sport participants

Abstract: Athletes participating in high-risk sports consistently report higher scores on sensation-seeking measures than do low-risk athletes or non-athletic controls. To determine whether genetic variants commonly associated with sensation seeking were over-represented in such athletes, proficient practitioners of high-risk (n = 141) and low-risk sports (n = 132) were compared for scores on sensation seeking and then genotyped at 33 polymorphic loci in 14 candidate genes. As expected, athletes participating in high-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The reasons for this trend may be behavioral or physiological or both. Behaviors modulated by this SNP include addiction [64, 65], aggression [66, 67], participation in high risk sports [68], and hyper-active impulsivity (in people with attention deficit hyperactivity disorder) [69]. Met carriers have greater hostility and aggression, supporting a behavioral explanation for this trend [63].…”
Section: Val66met In Tbimentioning
confidence: 99%
“…The reasons for this trend may be behavioral or physiological or both. Behaviors modulated by this SNP include addiction [64, 65], aggression [66, 67], participation in high risk sports [68], and hyper-active impulsivity (in people with attention deficit hyperactivity disorder) [69]. Met carriers have greater hostility and aggression, supporting a behavioral explanation for this trend [63].…”
Section: Val66met In Tbimentioning
confidence: 99%
“…The sensation seeking scores could be affected by some other factors such as hormonal changes (Guszkowska & Bołdak, 2010;Özdemir, 2007), and genetic variants (Guszkowska & Bołdak, 2010;Thomson et al, 2015). Gender could also be another substantial factor in sensation seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no differences were noted between UM participants and the norm group on disinhibition as well as thrill and sensation seeking scales, which may suggest that ultramarathon runners do not seek stimulation through the use of psychoactive substances nor they seem eager to take part in typical extreme sports disciplines ( Hughes et al, 2003 ). Moreover, Jack and Ronan (1998) showed that marathon runners score significantly lower an all subscales of the Sensation Seeking Scale V than do people who engage in extreme sports such as paragliding, parachuting, car racing, and mountain climbing. Potgieter and Bisschoff (1990) found that marathon runners assess their sport as less risky than rugby and scored lower on the thrill and adventure seeking scale than did rugby players.…”
Section: Introductionmentioning
confidence: 99%